Prevalence of Rift Valley Fever among Ruminants, Mayotte - Cêtre-Sossah, Catherine (Centers for Disease Control and Prevention, 2012)
Rift Valley fever threatens human and animal health. After a human case was confirmed in Comoros in 2007, 4 serosurveys among ruminants in Mayotte suggested that Rift Valley fever virus had been circulating at low levels since 2004, although no clinical cases occurred in animals. Entomologic and ecologic studies will help determine outbreak potential.